A pilot single centre, double blind, placebo controlled, randomized, parallel study of Calmagen® dermaceutical cream and lotion for the topical treatment of tinea and onychomycosis - Manoj Parekh; Girisha Ramaiah; Prachi Pashilkar; Ranjani Ramanujam; Peter Johnston; Leodevico L. Ilag (BMC, 2017)
Abstract Background Most of the current anti-fungal treatments are chemical-based, fungistatic, have low efficacy in the treatment of tinea and toxicity concerns, while onychomycosis remains recalcitrant to most antifungal therapies. The study aimed to establish the fungicidal, efficacy and safety profile of Calmagen® dermaceutical cream and lotion containing AMYCOT® as a topical treatment in patients with severe to very severe presentations of fungal skin (tinea) and nail infections (onychomycosis). Methods A randomized, placebo-controlled, double blind, parallel, single centre study was conducted on 28 subjects with severe to very severe tinea or onychomycosis. All patients were randomized in a ratio of 1:1 for treatment or placebo group. Subjects in the treatment arm received Calmagen® cream or lotion, while subjects in the placebo arm received a similar inert topical preparation. Tinea subjects were treated with cream for four weeks, while onychomycosis subjects were treated with lotion for 12 weeks. Mycological cure, the primary endpoint, was assessed by three parameters: KOH (potassium hydroxide) smear, fungal culture and live spore count. Clinical cure was defined as Investigator Global Assessment (IGA) response of 'cleared' or 'excellent'. Results All three parameters constituting mycological cure were confirmed in 92.8% (13/14) of subjects in the treatment arm, while all 14 subjects in the placebo arm remained positive for KOH smear. Calmagen® cream and lotion treatment showed a significant improvement in all three parameters: KOH smear, (95% CI (Calmagen): 79.4, 100.0; 95% CI (placebo): 0.0, 0.0; p < 0.0001); fungal culture (95% CI (Calmagen); 100.0, 100.0; 95% CI (Placebo): 17.0, 100.0; p < 0.0019); and live spore count (95% CI (Calmagen): 100.0, 100.0; 95% CI (Placebo): 17.0, 100.0; p < 0.0019). Clinical cure was achieved in all subjects in the treatment arm while none in the placebo arm were clinically cured. No treatment-related adverse effects were observed in either group. Conclusions The Calmagen® cream and lotion containing AMYCOT® represent a potentially safe and efficacious natural alternative in the treatment of Tinea and onychomycosis. Trial registration This trial has been registered with the clinical trial registry-India (CTRI; registration number: CTRI/2012/03/002522 ).